QUESTIONS OF FURTHER IMPROVEMENT OF THE BUSINESS MANAGEMENT SYSTEM - Imodinov Khamidillo Soyibjonovich; Kadirov Shukhratbek Qutbiddinovich (Scholar Express Journals, 2022)
The article examines the specificity and objective necessity of innovative development aimed at improving risk management in the development of business entities, and also discusses issues of further improving the business management system.
Keywords: Risk; entrepreneurship; management; investment; innovation process